Adaptations to Climatic Variability: Irrigation and Settlement Patterns in Early Medieval Rajasthan. (April 2014) - Kumar, Mayank
This Unlike all other elements in nature, water has played a role in all societies at all times. It is therefore a truly universal resource. Water is simultaneously always particularistic and in flux, varying from place to place and from time to time. This inherent dualism—the simultaneous embodiment of the universal and the particular—makes water particularly interesting in a comparative perspective since it has implications for how social development at different times and in different places can be made intelligible. These characteristics combined mean that it is possible to reconstruct, describe, delineate and understand its movement and role in nature and in society and at the same time evade the problems created by natural or biological determinism and social constructionism.